Everolimus with paclitaxel and carboplatin as first-line treatment for metastatic large-cell neuroendocrine lung carcinoma: a multicenter phase II trial - Christopoulos, Petros; Thomas, Michael (Annals of oncology, 2017)
AbstractBackground. Large-cell neuroendocrine carcinoma of the lung (LCNEC) is a rare disease with poor prognosis and limited treatment options. Neuroendocrine